Porokeratosis ptychotropica: a rare manifestation with typical histological exam - John Verrinder Veasey; Monique Coelho Dalapicola; Rute Facchini Lellis; Adriana Bittencourt Campaner; Thiago da Silveira Manzione; Maria Clarissa de Faria Soares Rodrigues (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Porokeratosis is a disorder of epidermal keratinization characterized clinically by a distinctive ridge-like border, and histologically by cornoid lamellae. The known clinical variants of porokeratosis are: classic porokeratosis of Mibelli, disseminated superficial (actinic) porokeratosis (DSAP), porokeratosis palmaris et plantaris disseminata, linear porokeratosis and punctate porokeratosis. In 1995, a seventh form was described as porokeratosis ptychotropica: a verrucous form resembling psoriasis involving the gluteal cleft presenting on the histological exam multiple cornoid lamellae. There are very few reports in the literature of this clinical variant. The present study describes the case of a healthy male presenting gluteal hyperkeratotic plaques for 22 years. He had been to several dermatologists, none of them had achieved a definitive diagnosis. We present a typical clinical presentation and its dermoscopy findings, in addition to histological examination that confirmed the diagnosis.